Reduction of Knee Q Angle Using Custom Foot Orthoses in Flat Foot Patients - Prasetyo Catur Utomo; Atika Febri Anggriani (Poltekkes Kemenkes Surakarta, 2025)
Background: Flat foot is the most prevalent musculoskeletal condition. Research indicates that between 20 and 30 % of youngsters worldwide suffer from flat feet. In addition to being a static alignment issue of the ankle and foot, flat foot is progressive and can contribute to aberrant dynamic function of other lower limbs. This condition directly affected the degree of q angle. The purpose of this study was to compare the degree of q angel knee joint, before and after the use of custom foot othosis in the study sample Methods: This is a quasi-experimental study with one group pre and post test design to determine the effect of using custom foot orthoses on reducing the degree of Q angle in flat foot. The total number of research samples is 26. The Wilcoxon test was used in this study to analyze the impact of the orthosi. Results: Based on the results of wilcoxon tests show that the p value is < 0.001 (p-value < 0.05), there was a significant difference in the use of custom foot orthoses before the intervention and after the intervention by 5.80. As a result. There was a significant difference in the use of custom foot orthoses before the intervention and after the intervention in reducing the degree of Q angle knee joint. Conclusion: The use of custom foot orthoses can significantly reduce the degree of Q angle knee joint of the study subjects. It is recommended to use orthosis to improve the degree of the Q angle.